The immunological perspective of major depressive disorder: unveiling the interactions between central and peripheral immune mechanisms - Wenli Jiao; Jiayi Lin; Yanfang Deng; Yelin Ji; Chuoyi Liang; Sijia Wei; Xi Jing; Fengxia Yan (Journal of Neuroinflammation)
Abstract Major depressive disorder is a prevalent mental disorder, yet its pathogenesis remains poorly understood. Accumulating evidence implicates dysregulated immune mechanisms as key contributors to depressive disorders. This review elucidates the complex interplay between peripheral and central immune components underlying depressive disorder pathology. Peripherally, systemic inflammation, gut immune dysregulation, and immune dysfunction in organs including gut, liver, spleen and adipose tissue influence brain function through neural and molecular pathways. Within the central nervous system, aberrant microglial and astrocytes activation, cytokine imbalances, and compromised blood-brain barrier integrity propagate neuroinflammation, disrupting neurotransmission, impairing neuroplasticity, and promoting neuronal injury. The crosstalk between peripheral and central immunity creates a vicious cycle exacerbating depressive neuropathology. Unraveling these multifaceted immune-mediated mechanisms provides insights into major depressive disorder’s pathogenic basis and potential biomarkers and targets. Modulating both peripheral and central immune responses represent a promising multidimensional therapeutic strategy.